Digital Transformation of Public Service and Administration - Mukesh Kumar Mishra (ZBW – Leibniz Information Centre for Economics, 2020)
This paper presents the results of a process tracing study of digital transformation in India. As the world embraces the revolution 4.0, emerging technologies such as 5G, Artificial Intelligence, among others, will transform governance efficiency and effectiveness. As the current revolution sweeps, the world and the IoT ride the wave, the reality here is that, governments of the future are destined to be digital by default. We need to prepare for this transformation for the future administration which will be digital. Government have to set for themselves Political Objectives to achieve greater trust in system, including through responsiveness and transparency, and by providing opportunities for greater engagement by service users and citizens in general.
Keywords: 330; Digital Transformation; Smart Administration